Endoscopic Versus Microscopic Retrosigmoid Approach for Vestibular Schwannoma Resection - Fareeha Nisar; Zanib Javed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Vestibular schwannomas are benign cerebellopontine angle tumours for which surgical management has evolved toward preservation of neurological function and quality of life. The retrosigmoid approach remains a commonly used corridor, traditionally performed with the operating microscope. However, limitations in visualization, particularly within the internal auditory canal, have lead to increasing adoption of endoscopic techniques. This review evaluates current evidence comparing fully endoscopic, endoscopic-assisted, and conventional microscopic retrosigmoid approaches. The most robust comparative data demonstrate that fully endoscopic surgery achieves outcomes comparable to microscopy in terms of gross total resection and facial nerve preservation. Endoscopic approaches offer improved visualization of concealed anatomical regions and may enhance extent of resection, especially in tumours with intracanalicular extension. Additionally, reduced surgical invasiveness has been associated with improved postoperative recovery and decreased morbidity. Endoscopic-assisted microsurgery remains a widely practiced transitional technique, combining the benefits of both modalities. Despite these advantages, endoscopic assisted technique is more practical in resource limited settings than fully endoscopic. Keywords: Vestibular Schwannoma, Retrosigmoid approach, Miscroscopic surgery, Endoscopic